Intraoperative vascular anastomosis occlusion due to cold agglutinin disease during brain surgery: a case report - Kazuma Kitamura; Mayumi Nakanishi; Naokazu Fukuoka; Kumiko Tanabe; Yoshinori Kamiya (JA Clinical Reports)
Abstract Background Cold agglutinin disease (CAD) is an autoimmune hemolytic anemia that induces blood coagulation and hemolysis upon exposure to cold temperatures. Strict temperature control is essential to mitigate these effects, especially during surgical procedures where hypothermia is possible. Case presentation A 57-year-old male, 165 cm and 72 kg, diagnosed with CAD, underwent cerebral vascular anastomosis. Intraoperatively, mean arterial pressure was maintained at or above 65 mmHg with phenylephrine administration, while body temperature was rigorously controlled between 36.5 °C and 37.5 °C using forced-air warming blankets and heated intravenous infusions. Despite these measures, thrombotic occlusion occurred, necessitating surgical thrombus removal, intravenous heparin administration, and irrigation of the surgical field with warmed saline followed by re-anastomosis. The anastomosis remained patent without recurrence of thrombus formation thereafter. Conclusion Preventing hypothermia is extremely important in the anesthesia management of CAD patients. However, careful attention must also be paid to temperature regulation in the surgical field.